DA’WAH MODEL OF PROPHET MUHAMMAD IN MADINA - Mubasyaroh Mubasyaroh (P3M STAIN Kudus, 2016)
In Medina, Prophet Muhammad’s da’wah covered all areas of life. The writer focused on the setting system of social life. The Medina society was heterogeneous so he should have good strategy in order to make his preach successful. Muhammad SAW also served as educators, counselors, politicians, leaders and statesmen to various people who had different character and nature from various nation, tribe, religion, language, tradition and culture. The da’wah model of the Prophet Muhammad in Medina was divided into public relations management system and the system of government and politics. The Medina Charter concluded by asserting that each dispute among the Muslims in Medina should be returned to the provisions of Allah and His Messenger. In general, the model of Prophet Muhammad’s da’wah was to build mosques, unite the Muhajirin and the Anshar companions and make peace with non-Muslims (the Jews) as stipulated in the Medina Charter consists of 47 chapters.